Fluktuasi dan Peramalan Harga Cabai Rawit di Kabupaten Malang - Lia Rohmatul Maula; Titis Surya Maha Rianti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2021)
Cayenne pepper is one of the strategic horticultural commodities where price increases contributed to the amount of cayenne pepper inflation that occurred in Indonesia. This volatility in chili prices is closely related to the supply and demand for chilies. Along with the fluctuation of chili prices, a research was conducted on the price fluctuation of chili in Malang Regency. This study aims to determine the price fluctuation of cayenne pepper and forecast the price of cayenne pepper in Malang Regency. In this study, researchers used time series data on monthly cayenne pepper prices for 2017-2020. Analysis of price fluctuations was carried out by descriptive statistics and price forecasting per month was carried out using the ARIMA model. The results of this study show that the highest price fluctuation of cayenne pepper occurred in February 2017 amounting to IDR 123,164 / kg and the lowest price of cayenne pepper occurred in October 2017 of IDR 12,974 / kg. Forcasting the price of cayenne pepper in 2021 to 2022, it is found that the highest price occurs in November 2022 of IDR 102,840/Kg and the lowest is in March 2021 of IDR 72,065/Kg.